Islam dan Relasi Sosial Pandangan Al-Qur’an Tentang Multikulturalisme - Supriadi AM (Jurnal Asy-Syukriyyah, 2017)
Al-Qur’an is not only speaks to muslem, but to talk to many people, such as cristians, jews, polytheists of Mecca and others, but also the different communities which proves that al-Quranin not only talked to on religious community, but also speaks a lot parties (communities). This researchmethode is used a descriptive analysis, which is theme of different culture are currently being in various perpektive. It analyzed the point of view commentators manner, analyzed the data from the verses and the opinion of mufassir. The objective of this Paper is to investigate how the quran the hudan linnas be the originator of the universality in teachings Islam in life wich values diversity and believes as a necessity in the concept of multicultural.